USE OF SCALES TO ESTIMATE POPULATIONS OF MITES Tetranychidae AND SAMPLE PRESENCE- ABSENCE FOR Phytoseiidae IN YUCCA CROPS - LENIS, JORGE IVÁN; BRAUN, ANN R.; MESA-C., NORA CRISTINA; DUQUE, MYRIAM C. (Revista Colombiana de Entomología, 1993)
Direct count of tetranychid mites in field or laboratory is a very inefficient and tedious task, due to the high populations that develóp on cassava. For this reason a faster and configurable method needs to be developed. On these bases a work was carried out to established the relationship between the population scale used in the field and direct countings of mites in the laboratory, and to observe the stability of such a scale on different plant strata and crop ages. Concerning the phytoseiid mites, it was pretended to verify the presence-absence score between field and laboratory counts. This study was developed during two crop cycles al CIATPalmira, using the cassava variety CMC40. Counts were made every two weeks in 20 plots of 144 plants each. A central plant was chosen and every other leaf was picked after the first completely developed leaf. On individual leaves from 5 randomly selected plants phytophagous mites were counted under the stereo-microscope discriminating stadia and species. All phytoseiid mites present were collected on each evaluated node; on each level of the plant, a three-minute sample was taken of all the tetranychids mites for taxonomic purposes. It was possible to determine the coefficients that allow conversion of field scores into real population estimates of cassava tetranychid mites. Confidence limits for the sampling procedure were also determined. An error percentage was established for presence-absence evaluations of phytoseiid mites. Additional information was obtained on the stability of the field scale on the various plant strata.